OECD Water Governance Approach to Optimizing Drainage System in Semarang - Kusumadewi, Adlina; Adi, Henny Pratiwi; Wahyudi, Slamet Imam (Journal of Advanced Multidisciplinary Research, 2025)
Effective drainage systems are crucial for managing stormwater, preventing flooding, and promoting urban sustainability. However, rapid urbanization and climate change exacerbate drainage challenges in cities like Semarang, where poor infrastructure often struggles with heavy rainfall and tidal floods. Despite proactive efforts, such as participation in the Water as Leverage program, the city's drainage system faces significant challenges, including financial limitations and poor coordination between stakeholders. This study applies the Organization for Economic Co-operation and Development (OECD) Water Governance Principles to analyze the governance framework of Tenggang drainage system, identifying gaps and proposing improvements. A qualitative, descriptive approach was used, collecting primary data through interviews with government and community stakeholders, alongside secondary data from literature and document analysis. The results highlight the need for clearer roles and responsibilities, better coordination across government levels, and enhanced public participation. It was also found that integrating policies across sectors and fostering innovation could significantly improve the system's efficiency and sustainability. Additionally, strengthening transparency, trust, and community engagement is essential for achieving more inclusive governance. This study concludes that aligning Semarang’s drainage management with the OECD principles can lead to a more resilient, efficient, and sustainable system that addresses both current challenges and future water management needs.